Extensive Air Showers with Unusual Structure - Beznosko, Dmitriy; Beisembaev, Rashid; Baigarin, Kanat; Beisembaeva, Elena; Dalkarov, Oleg; Ryabov, Vladimir; Sadykov, Turlan; Shaulov, Sergei; Stepanov, Aleksei; Vildanova, Marina; Vildanov, Nikolay; Zhukov, Valeriy (ISVHECRI 2016, 2016)
The total of 23500 Extensive Air Showers (EAS) with the energy above 1016 eV have been detected during the 3500 hours of Horizon-T (HT) detectors system operations before Aug 2016. Among these EAS, more than a thousand had an unusual spatial and temporary structure that showed the pulses with several maxima (modals or modes) from several detection points of the HT at the same time. These modes are separated in time from each other starting from tens to thousands of ns. These EAS have been called multi-modal. Analysis shows that the multi-modal EAS that have been detected by Horizon-T have the following properties: 1. Multi-modal EAS have energy above 1017 eV. 2. Pulses with several modes are located at large distances from EAS axis. The overview of the collected data will be provided. General comments about the unusualities of the structure of the multi-modal EAS will be presented.